Pemanfaatan Tanaman Pekarangan Sebagai Bahan Obat Tradisional Oleh Battra Suku Melayu di Desa Samustida Kabupaten Sambas - Dina Loresa; Fathul Yusro; Yeni Mariani (Fakultas Teknik, 2023)
The forest provides various medicinal plants, but many plants that come from the forest have been cultivated in the yard to make it easier to take the plants when you want to use them. This research aims to study the types of garden plants used for medicine by the Battra of the Malay tribe in the Samustida village, Sambas Regency. This research was carried out in Samustida village, Teluk Keramat District, Sambas Regency. This research uses the survey method by interviewing the battra, where the battra is determined with the purposive sampling technique. The research results show that the Battra of the Malay tribe in Samustida Village uses 61 medicinal plants in their home grounds, with the highest plant family using Zingiberaceae (8 species). The parts of the plant that are used the most are the leaves (41%) by boiling (28.86%) and drinking (43%).